2020
DOI: 10.1371/journal.pone.0235262
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experience of agency and respect in maternity care by type of insurance in California

Abstract: Objective Public insurance (Medicaid) covered 42% of all U.S. births in 2018. This paper describes and analyzes the self-reported experiences of women with Medicaid versus commercial insurance relating to autonomy, control and respectful treatment in maternity care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
(45 reference statements)
3
25
0
Order By: Relevance
“…Access to community birth is an issue that needs to be addressed. There are both the lack of health insurance coverage for community birth and the very low reimbursement rates at birth centers, which limit birth centers’ ability to care for patients with Medicaid insurance 7,8 . These barriers require a policy response.…”
Section: Can We Influence Decisions About Where To Give Birth In the ...mentioning
confidence: 99%
“…Access to community birth is an issue that needs to be addressed. There are both the lack of health insurance coverage for community birth and the very low reimbursement rates at birth centers, which limit birth centers’ ability to care for patients with Medicaid insurance 7,8 . These barriers require a policy response.…”
Section: Can We Influence Decisions About Where To Give Birth In the ...mentioning
confidence: 99%
“…3 Mistreatment was more common among women of color, including Black, Hispanic, Indigenous, and Asian women, and especially low-income women of color-27% of whom reported mistreatment-compared with lowincome white women (19%). 3 In California, women with Medi-Cal (California's Medicaid) coverage, who are disproportionately Black or Latina, 6 are more likely than women with private insurance to report unfair treatment on the basis of race or ethnicity (6.5% versus 2.3%, respectively), language spoken (7.4% versus 1.7%), and--among English speakers especially--insurance status (9.0% versus 0.7%) during their intrapartum and postpartum hospital visit. 6 Experience of mistreatment and racism can be a deterrent to seeking maternity care, which further perpetuates health inequities.…”
Section: Introductionmentioning
confidence: 99%
“…3 In California, women with Medi-Cal (California's Medicaid) coverage, who are disproportionately Black or Latina, 6 are more likely than women with private insurance to report unfair treatment on the basis of race or ethnicity (6.5% versus 2.3%, respectively), language spoken (7.4% versus 1.7%), and--among English speakers especially--insurance status (9.0% versus 0.7%) during their intrapartum and postpartum hospital visit. 6 Experience of mistreatment and racism can be a deterrent to seeking maternity care, which further perpetuates health inequities. 11,12 Moreover, racism can affect medical decision making 13 and provider-patient communication, 14 which may result in medical emergencies being overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details of the survey methodology are available elsewhere [34]. Data from this survey have previously been used to examine women's experiences in intrapartum care [35][36][37][38]. This study is not considered human subjects research, as it uses publicly available, de-identified data.…”
Section: Introductionmentioning
confidence: 99%